2006
DOI: 10.3168/jds.s0022-0302(06)72352-9
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Responses of Mexican Holstein Cows to US Sire Selection

Abstract: Genetic relationships between 2 fertility traits and milk production were investigated using mature-equivalent lactation records of 55,162 daughters of 1,339 Holstein sires in Mexico and 499,401 daughters of 663 Holstein sires in the northeastern United States. Data sets contained yields in first and second lactation, age at first calving (AFC), and calving interval (CI). There were 474 US sires in common between countries. A herd-year standard deviation criterion defined nonoverlapping low- (< or = 1,300 kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
3
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
1
5
3
6
Order By: Relevance
“…Also, consistent with the current results, Ruiz-Sánchez et al (2007) reported that the genetic correlations between AFC and MY were negative regardless of herd level. The genetic correlation between AFC and MY in this study was slightly larger than those in previous reports for Holstein cows that ranged from −0.20 to −0.33 (Pirlo et al 2000;Mäntysaari et al 2002;Cienfuegos-Rivas et al 2006), although positive genetic and phenotypic correlations between AFC and MY have also been reported in Sahiwal cattle in semi-arid Kenya (Ilatsia et al 2007). Also, generally consistent with the results of this study, Ghavi Hossein-Zadeh and Ardalan (2011) reported that genetic correlations among milk traits were consistently high in Holstein dairy cows.…”
Section: Discussioncontrasting
confidence: 77%
“…Also, consistent with the current results, Ruiz-Sánchez et al (2007) reported that the genetic correlations between AFC and MY were negative regardless of herd level. The genetic correlation between AFC and MY in this study was slightly larger than those in previous reports for Holstein cows that ranged from −0.20 to −0.33 (Pirlo et al 2000;Mäntysaari et al 2002;Cienfuegos-Rivas et al 2006), although positive genetic and phenotypic correlations between AFC and MY have also been reported in Sahiwal cattle in semi-arid Kenya (Ilatsia et al 2007). Also, generally consistent with the results of this study, Ghavi Hossein-Zadeh and Ardalan (2011) reported that genetic correlations among milk traits were consistently high in Holstein dairy cows.…”
Section: Discussioncontrasting
confidence: 77%
“…The sire-herd effect on AF, measured as a proportion of phenotypic variance, was larger in this study (0.10) than the additive genetic effects. This magnitude of the sire-herd variance may imply that daughters of specific sires may receive shared management practices, creating a confounding between sire genetic and environmental effects (Pirlo et al, 2000;Cienfuegos-Rivas et al, 2006), which may also explain why estimates of heritability for this trait span such a wide range across studies. The sire-herd proportion of phenotypic variance was generally small for other traits (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…recommended grouping animals by sire PTA milk, rainfall, fat to protein ratio, and standard deviation of milk yield instead of by country borders. This has the potential to increase genetic progress by increasing the accuracy for such international genetic selection programs.The use of sires across multiple countries within the dairy industry has an effect on milk yield, age at first calving, and milk fat(Ceron-Munoz et al, 2004a;Ceron- Munoz et al, 2004b;Cienfuegos-Rivas et al, 2006;Costa et al, 2000). The genetic correlations for milk yield and age at first calving were inconsistent between Mexico and the United States in the study conducted byCienfuegos-Rivas et al (2006).…”
mentioning
confidence: 91%
“…This has the potential to increase genetic progress by increasing the accuracy for such international genetic selection programs.The use of sires across multiple countries within the dairy industry has an effect on milk yield, age at first calving, and milk fat(Ceron-Munoz et al, 2004a;Ceron- Munoz et al, 2004b;Cienfuegos-Rivas et al, 2006;Costa et al, 2000). The genetic correlations for milk yield and age at first calving were inconsistent between Mexico and the United States in the study conducted byCienfuegos-Rivas et al (2006). A negative correlation existed between milk yield and age at first calving when analyzed within countries, but the correlation was positive when analyzed between countries(Cienfuegos- Rivas et al, 2006) Ceron-Munoz et al (2004a.).…”
mentioning
confidence: 92%
See 1 more Smart Citation